THE EFFECT OF RED AND YELLOW CARBON QUANTUM DOTS (CQDS) IN TIO2 PHOTOANODES FOR DSSC APPLICATION - Al-Afandy, Farhan Nur; Diantoro, Markus; Pujiarti, Herlin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The exploration of Dye-Sensitized Solar Cells (DSSC), especially regarding the photoanode, is steadily advancing. widely recognized, the photoanode plays a key role in absorbing light and facilitating electron generation, which is essential for the efficiency of Dye-Sensitized Solar Cells (DSSC). TiO2 is frequently used as photoanode due to its excellent stability and ability to effectively support dye molecules. However, in terms of enhancing light absorption and the electron transfer rate, doping with Carbon Quantum Dots (CQDs) in TiO2-based photoanodes has gained attention as a promising approach to improve efficiency. In this research, Carbon Quantum Dots (CQDs) were added to TiO2 to enhance its properties. Red CQDs and Yellow CQDs were incorporated into TiO2 at a concentration of 5%. The resulting composite materials were characterized using XRD, UV-Vis, and I-V measurements with a solar simulator. The XRD pattern confirmed the crystalline structure of TiO2 with incorporated CQDs. The optical properties of the CQD-TiO2 composites were analyzed through UV-Vis spectroscopy, revealing changes in light absorption. The DSSC performance parameters, including Jsc, Voc, FF, and η, were determined through I-V characterization using a solar simulator. The best DSSC performance was obtained by the sample with the addition of 5% Yellow CQDs, with an efficiency of 3.42%